Differential Expression of DeltaFosB in Reward Processing Regions Between Binge Eating Prone and Resistant Female Rats - Quansah Amissah, Richard; Chometton, Sandrine; Calvez, Juliane; Guèvremont, Genevieve; Timofeeva, Elena; Timofeev, Igor (Frontiers in Systems Neuroscience, 2020)
Binge eating (BE) is characterized by the consumption of large amounts of palatable food in a discrete period of time and compulsivity. Even though BE is a common symptom in bulimia nervosa, binge eating disorder, and some cases of other specified feeding or eating disorders, little is known about its pathophysiology. We aimed to identify brain regions and neuron subtypes implicated in the development of binge-like eating in a female rat model. We separated rats into binge eating prone (BEP) and binge eating resistant (BER) phenotypes based on the amount of sucrose they consumed following foot-shock stress. We quantified deltaFosB (ΔFosB) expression, a stably expressed Fos family member, in different brain regions involved in reward, taste, or stress processing, to assess their involvement in the development of the phenotype. The number of ΔFosB-expressing neurons was: 1) higher in BEP than BER rats in reward processing areas (medial prefrontal cortex (mPFC), nucleus accumbens (Acb), and ventral tegmental area (VTA)); 2) similar in taste processing areas (insular cortex and parabrachial nucleus); 3) higher in the paraventricular nucleus of BEP than BER rats, but not different in the locus coeruleus, which are stress processing structures. To study subtypes of ΔFosB-expressing neurons in the reward system, we performed in situ hybridization for glutamate decarboxylase 65 and tyrosine hydroxylase mRNA after ΔFosB immunohistochemistry. In the mPFC and Acb, the proportions of gamma-aminobutyric acidergic (GABAergic) and non-GABAergic ΔFosB-expressing neurons were similar in BER and BEP rats. In the VTA, while the proportion of dopaminergic ΔFosB-expressing neurons was similar in both phenotypes, the proportion of GABAergic ΔFosB-expressing neurons was higher in BER than BEP rats. Our results suggest that reward processing brain regions, particularly the VTA, are important for the development of binge-like eating.